Dispersion Characteristics of the Propagation Waves in the Gyroelectric Semiconductor Waveguides - Mališauskas, V.; Plonis, D. (Elektronika ir Elektrotechnika, 2010)
Presented general electrodynamical and mathematical model of the open cylindrical round cross-section gyroelectric semiconductor waveguides. Created general algorithm and program in MATLAB© for calculations dispersion characteristics of the propagation wave’s in the waveguides. Are investigated characteristics of the waves HE11, EH11 and HE12 in 0.01– 0.1 GHz·m normalized frequency range. The waves propagated in n, p-InAs, n, p-InP semiconductor and semiconductor-dielectric waveguides, and they are in an external con-stant longitudinal magnetic flux density 1 T. Waveguide parameters established: working frequency range, central frequency and broad-band width.